STRESS LEVEL OF PREGNANT WOMEN DURING THE PANDEMIC COVID-19 IN THE VILLAGE OF KALIANYAR NGRONGGOT DISTRICT NGANJUK REGENCY - Muchsin, Enur Nurhayati (PRIMA WIYATA HEALTH, 2021)
Pregnancy is a period in which the body of a pregnant woman undergoes changes, both physiologically and psychologically. One of the psychological changes that occur is stress. Stress is the body's response that is non-specific in nature to any load demands and reaction patterns and general adaptations, pregnant women and families need to work together in overcoming stress during the COVID-19 pandemic. The purpose of this study was to determine the stress level of pregnant women during the Covid-19 pandemic. The research design was descriptive. The results from 24 respondents, respondents experienced moderate stress, 20 respondents (83%). A small part of the respondents experienced severe stress 4 respondents (17%). This is influenced by several factors, age, education, occupation, pregnancy history, gestational age, information about Covid-19, sources of information about Covid-19, antenatal care (ANC). pregnant can control stress during pregnancy . support from family and always implementing health protocols and thinking positively during pregnancy.